2011
DOI: 10.2310/7290.2010.00050
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Computed Tomography of Single Breast Cancer Microcalcifications in Vivo

Abstract: Microcalcification is a hallmark of breast cancer and a key diagnostic feature for mammography. We recently described the first robust animal model of breast cancer microcalcification. In this study, we hypothesized that high-resolution computed tomography (CT) could potentially detect the genesis of a single microcalcification in vivo and quantify its growth over time. Using a commercial CT scanner, we systematically optimized acquisition and reconstruction parameters. Two ray-tracing image reconstruction alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The injection volume and HA concentration were readily tailored providing a straightforward and reproducible model for creating microcalcifications of known HA concentration for investigating X-ray contrast agents. Breast microcalcifications have also been biologically-induced in mice and rats via implanted cancer cells [44] and delivery of exogenous growth factors [4547], respectively, but these models require separate measurements to quantify the HA concentration or microcalcification burden rather than offering a priori control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The injection volume and HA concentration were readily tailored providing a straightforward and reproducible model for creating microcalcifications of known HA concentration for investigating X-ray contrast agents. Breast microcalcifications have also been biologically-induced in mice and rats via implanted cancer cells [44] and delivery of exogenous growth factors [4547], respectively, but these models require separate measurements to quantify the HA concentration or microcalcification burden rather than offering a priori control.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo models of breast microcalcifications have been developed in mice using implanted tumor cells [44] and in rats using exogenous growth factors [4547]. These models are more biologically-relevant and will be useful for future investigations for the targeted delivery of BP-Au NPs and radiographic imaging in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…The in vivo murine model of microcalcifications developed in this study was an extension of an ex vivo tissue model we previously reported . Other in vivo models of breast microcalcifications have been previously developed in rodents using implanted tumor cells and exogenous growth factors. These models are more biologically relevant for the spontaneous formation and growth of microcalcifications, but the amount of mineral that is deposited varies between animals and requires additional verification. Furthermore, the formation of microcalcifications in these models is preceded by tumor formation, in contrast to the normal disease progression, and the presence of tumor tissue may create additional model variability due to differences in the X-ray attenuation of the background tissue between animals.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to mice, with an adult size of 300-500 g, rats are large enough for structures, such as microcalcifications, to be differentiated by PET within a mammary gland. It has been reported that aging rats develop microcalcifications in their mammary glands (21) and, more recently, that they can even be implanted with, or stimulated to grow, mammary calcifications (22). Here, we report the use of aged, female, retired breeder Sprague-Dawley rats as models for both normal and pathologic human breast tissue microcalcifications without any artificial microcalcification growth induction.…”
mentioning
confidence: 97%